THE EFFECT OF GUIDED WRITING STRATEGY ON THE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXTS - Rosa Dian Utari; Amrin Saragih (Universitas Negeri Medan, 2016)
This study deals with the effect of Guided Writing Strategy on the students’ abilityin writing procedure texts. The objective of this study is to find out whetherGuided Writing Strategy significantly affects students’ ability in writing proceduretexts. This study conducted by experimental research. The population of thisresearch was grade X students of SMA swastaHarapanBangsa Kuala. The samplewas class X1, X2 with 60 students. The students were divided into experimentaland control group. The experimental group was taught using Guided WritingStrategy and control group was taught without Guided Writing Strategy. The datawere analyzed by using t-test formula to find out the t-observed, which wascompared to the t-table in level 0.05. it is found that the t-observed is higher thant-table (t-observed = 4.527 > t-table = 2.000 ; p = 0.05) meaning that GuidedWriting Strategy significantly affects the students’ ability in writing procedure.